Peningkatan Kapasitas Masyarakat dalam Pengelolaan Homestay untuk Wisatawan - Faozen, Faozen; Juhanda, Juhanda; Siswanto, Edhi (LPkM Universitas Bakrie, 2025)
Community-based homestay management is one of the strategies in supporting the development of sustainable tourism and based on the local economy. However, there are still many homestay managers who face various obstacles, such as a lack of understanding of service standards, limitations in digital marketing, and a lack of implementation of sustainability concepts. This community capacity building program in homestay management aims to improve servicequality, digital marketing strategies, and environmentally friendly practices in homestay management in Sidomulyo Village, Jember Regency. The method used in this program is the Participatory Action Research approach. The results of this program show that after the training, 80% of tourists feel more satisfied with the homestay service, while 90% of managers start actively marketing their homestays through social media and online platforms. In addition, the concept of sustainability is on the rise, with 70% of homestay managers starting to implement waste sorting systems and reduce the use of single-use plastics. Despite this, the program still faces a number of challenges, such as limited funds for facility renovations, lack of ongoing assistance in digital marketing, and lack of cooperation with travel agents and tour operators.